Regulation of Corticosteroidogenic Genes by MicroRNAs - Stacy Robertson; Louise A. Diver; Samantha Alvarez-Madrazo; Craig Livie; Ayesha Ejaz; Robert Fraser; John M. Connell; Scott M. MacKenzie; Eleanor Davies (International Journal of Endocrinology)
The loss of normal regulation of corticosteroid secretion is important in the development of cardiovascular disease. We previously showed that microRNAs regulate the terminal stages of corticosteroid biosynthesis. Here, we assess microRNA regulation across the whole corticosteroid pathway. Knockdown of microRNA using Dicer1 siRNA in H295R adrenocortical cells increased levels of CYP11A1, CYP21A1, and CYP17A1 mRNA and the secretion of cortisol, corticosterone, 11-deoxycorticosterone, 18-hydroxycorticosterone, and aldosterone. Bioinformatic analysis of genes involved in corticosteroid biosynthesis or metabolism identified many putative microRNA-binding sites, and some were selected for further study. Manipulation of individual microRNA levels demonstrated a direct effect of miR-125a-5p and miR-125b-5p on CYP11B2 and of miR-320a-3p levels on CYP11A1 and CYP17A1 mRNA. Finally, comparison of microRNA expression profiles from human aldosterone-producing adenoma and normal adrenal tissue showed levels of various microRNAs, including miR-125a-5p to be significantly different. This study demonstrates that corticosteroidogenesis is regulated at multiple points by several microRNAs and that certain of these microRNAs are differentially expressed in tumorous adrenal tissue, which may contribute to dysregulation of corticosteroid secretion. These findings provide new insights into the regulation of corticosteroid production and have implications for understanding the pathology of disease states where abnormal hormone secretion is a feature.